(untitled) (Comprehensive Journal of Science, 2025)
There is a growing interest in natural ingredients that can be used as preservatives in the food industry and preservation. Among the natural materials that can be used for preservation are plant extracts that are extracted from some natural plants, such as thyme (Thymus vulgaris ), The current work aimed to study the efficiency of extracts and oils of local medicinal plant (thyme) in preserving fish. Two species of fresh, economical fish writhe(sparus aurata) sardines,( sardine pilchardus ) that are widely consumed were collected during May, 2023, each species divided into two group type, one of the two were treated with the extracts of these plants and the other group were treated with the oils of studied plants demonstrated the effectiveness of these herbs in preserving these fish. A comparison was made between the effectiveness of extracts and oils from these plants in preserving the fish studied. The results showed that there were differences between the samples before and after treatment. The results showed that there were differences between the types of solutions, indicating that the alcoholic extract is better than the aqueous and oil extracts in the process of preserving genetic fish and sardines. There are no differences between the types of plant used in the experiment, which are (thyme,) Whereas a concentration of 20% is better in the preservation process than a concentration of 10%.